Team Assisted Individualization Learning Model Assisted with Student Worksheet toward Mathematical Knowledge Competence - Ni Nyoman Puspa Widhi Saraswati; Gusti Ngurah Sastra Agustika (Jurnal Ilmiah Sekolah Dasar, 2020)
The ability of students to understand every material available in mathematics learning is not yet optimal. There are still obstacles such as the lack of self-confidence of students to believe that they are able to participate in any given mathematics learning. This causes students to become dependent with other students in each lesson. Based on these problems, this research was conducted with the aim to analyze the significant effect of the Assisted Individualization Team Learning Model Assisted by Student Worksheets on the competence of the fifth grade mathematics competencies of the Lieutenant Colonel Wisnu Cluster. This study is an experimental study with the Nonequivalent Control Group Design research design. The population of this study was 334 students. The sampling technique used in this study was cluster sampling. Data of mathematical knowledge competence is collected through essay tests with 5 valid and reliable questions. The results of the t-test analysis showed tcount> ttable ie 3.27> 2.01 at a significant level of 5% and dk = 51, so H0 was rejected and Ha was accepted, thus it can be concluded that the Learning Model Assisted Individualization Team Assisted Individualization Assisted by Student Worksheets significantly influenced the competence of Mathematical knowledge fifth grade students of the Lt. Col. Wisnu Cluster Group.